Knowledge Evolution of Digital Business Transformation: A Bibliometric Analysis and Emerging Research Trends - violeta nirmala; Yuli Alam (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
The rapid growth of Digital Business Transformation research has led to a significant increase in scientific publications; however, studies mapping the evolution of knowledge, intellectual structure, and emerging research trends remain limited. This study aims to analyze the knowledge evolution of Digital Business Transformation through a bibliometric review and identify future research directions. A descriptive quantitative bibliometric approach was employed using publication data retrieved from the Google Scholar database through Publish or Perish. The search strategy was based on keywords related to Digital Business Transformation, covering publications published between 2022 and 2026. The retrieved records were screened to remove irrelevant and duplicate documents, resulting in 987 publications that met the inclusion criteria. The selected articles were exported in RIS format and analyzed using VOSviewer through keyword co-occurrence analysis, including network visualization, overlay visualization, and density visualization, to identify the intellectual structure, thematic evolution, research maturity, and emerging topics. The findings indicate that the research landscape is still dominated by MSME digitalization, technology adoption, entrepreneurship, social media, and business performance. The overlay analysis reveals a shift from operational technology implementation toward strategic business transformation emphasizing business model innovation and value creation. This study contributes by proposing a Knowledge Evolution Framework and identifying promising future research themes, including Artificial Intelligence, Digital Capability, Digital Ecosystem, Human-Centered Digital Business, and Business Intelligence. These findings provide valuable insights for researchers and practitioners in developing adaptive digital business transformation strategies and future research agendas.